Gamma heat analysis in various power levels of RSG G.A. Siwabessy silicide core. (March 2020) - Rohanda, A; Waris, A; Kurniadi, R; Kiswanta,; Husnayani, I
Abstract: Reaktor Serba Guna G.A. Siwabessy (RSG-GAS, previous name MPR-30) is the largest research reactor in Southeast Asia that acts as a national facility to irradiate material. Gamma heat is a very important factor for the safety analysis in every material irradiation activity at the irradiation facility. Gamma heat is the main research topic of several forms of safety investigations at world research reactors. Gamma heat information is useful to predict the temperature of the material to be irradiated and negligence in predicting gamma heat can cause overheating. Gamma heat values are very dependent on the characteristics of the reactor core. Changes in reactor power can affect the core characteristics. RSG-GAS is designed to have a 30 MWth of nominal power but it is currently operated at 15 MWth power level. In this study observed changes in gamma heat as a function of reactor power and material target on the Central Irradiation Position (CIP) silicide core of RSG-GAS by using a modified GAMSET program. Modifications are made by adjusting the material and power configuration in the core. The results of the analysis show that gamma heat will be increase in accordance with the increase in power level in various material targets such as graphite (C), aluminium (Al), iron (Fe) and zirconium (Zr). Gamma heat also tends to increase according to the increase of atomic number target. Verification has been carried out with the results of calculations in the 35 MWth CEA Grenoble reactor with the smallest yield difference of 1.23% in the graphite target and 2.71% in the iron target.